2016
DOI: 10.1007/s00415-016-8360-4
|View full text |Cite
|
Sign up to set email alerts
|

The MRZ reaction as a highly specific marker of multiple sclerosis: re-evaluation and structured review of the literature

Abstract: MRZR is the most specific laboratory marker of MS reported to date. If present, MRZR substantially increases the likelihood of the diagnosis of MS. Prospective and systematic studies on the diagnostic and prognostic impact of MRZR testing are highly warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
97
1
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 115 publications
(111 citation statements)
references
References 71 publications
8
97
1
5
Order By: Relevance
“…It has been demonstrated that the intrathecal polyspecific humoral response of MS patients has Measles, Rubella and VZ viruses (MRV) as its most frequent component [101], providing a useful help for MS diagnosis. Moreover VZV infection is associated with higher risk of developing MS [102].…”
Section: Measles Rubella and Varicella Zoster (Vz) Virusesmentioning
confidence: 99%
“…It has been demonstrated that the intrathecal polyspecific humoral response of MS patients has Measles, Rubella and VZ viruses (MRV) as its most frequent component [101], providing a useful help for MS diagnosis. Moreover VZV infection is associated with higher risk of developing MS [102].…”
Section: Measles Rubella and Varicella Zoster (Vz) Virusesmentioning
confidence: 99%
“…The intrathecal polyspecific anti‐viral immune response is detected in most MS patients, but rarely in other neuroinflammatory diseases 6. These findings have also been confirmed in OCB negative contexts21 and in clinically isolated syndrome patients who subsequently converted to MS 22.…”
Section: Discussionmentioning
confidence: 72%
“…In a majority of MS patients, antibody‐secreting cells are present in the central nervous system, and locally produced immunoglobulin G (IgG) can be detected in the cerebrospinal fluid (CSF) as oligoclonal bands (OCB) 3. Curiously, an intrathecal humoral immune response targeting commonly encountered viruses, including measles, rubella, and varicella zoster virus (VZV) can be observed in most MS patients, as opposed to patients with other neuroinflammatory diseases 4, 5, 6, 7, 8. These antibodies constitute a minor fraction of the intrathecally synthesized antibodies and are believed to be irrelevant to the pathophysiology of MS 7.…”
Section: Introductionmentioning
confidence: 99%
“…По данным литературы, показа-Таблица 1. Частота встречаемости повышенных показателей интратекального гуморального иммунного ответа у больных РС и в группе сравнения тель специ фичности MRZR достигает 97,5% [19]. Важно, что положительная MRZR вовсе не свойственна острым заболеваниям ЦНС и редко наблюдается при хронических воспалительных и невоспалительных заболеваниях ЦНС [27,32].…”
Section: рисунок 1 частота выявления повышенных индексов антивирусныunclassified